(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
Combination systems represent an innovative approach to addressing the growing demand for energy-efficient heating solutions. By integrating multiple heating technologies, these systems offer enhanced efficiency, cost savings, and environmental benefits. This article examines the concept of combination systems, highlighting their advantages, applications, and potential challenges. From reducing carbon footprints to improving reliability and operational costs, combination systems provide a sustainable pathway to meet modern heating demands while aligning with global energy conservation goals. With advancements in technology and supportive policies, these systems are poised to play a pivotal role in the transition to sustainable energy use.